Color tuning of intrinsic white-light emission in anthracene-linker coordination networks. Issue 34 (21st August 2020) - Yu, Chengfeng; Wang, Xiaoling; Wu, Ting; Gu, Xiangwei; Huang, Wei; Kirillov, Alexander M.; Wu, Dayu
Abstract : We present two new Zn(ii ) anthracene-linker-driven coordination polymers that exhibit intrinsic white-light emission, which can be tuned under external stimuli, including thermal and mechanical grinding. Abstract : White light-emitting diodes (WLEDs) have aroused great attention due to their potential technological applications. In this work, we present two new Zn(ii ) anthracene-linker-driven coordination polymers that exhibit intrinsic white-light emission. The emission covers the whole visible spectrum at room temperature. The chromaticity coordinates of the broadband emission can be tuned under external stimuli, including thermal and mechanical grinding. The obtained coordination polymer materials emit a "warm" white light at room temperature suitable for indoor lighting applications as well as a "cold" white light at the cryogenic temperature. Hence, the well-defined structures and mechanically tunable emission provide an excellent opportunity for realizing their potential as white emitters in optoelectronics.